IMPLICATIONS OF BUDGET REFOCUSING POLICIES IN INDONESIA'S PANDEMIC COVID-19 - Kumba Digdowiseiso; Zaenal Arifin; Dwi Budi Sulistiyana; Ahmad Nabil Bintang (SEAN Institute, 2023)
Through the implementation of a budget refocusing policy, budget absorption in the administration of state finances during the COVID-19 epidemic in Indonesia has led to dynamic issues with the public finance system. Using a normative methodology and the aid of government policy tools, this study intends to explain and analyze the execution and effects of budget refocusing policies during the COVID-19 epidemic in Indonesia. Using secondary data from books, journals, articles, internet searches, and papers released by the Ministries of Finance, Home Affairs, and Statistics, the research method employs a qualitative descriptive literature analysis. This study may show that fiscal decentralization was used as a strategic policy to guide the implementation of budget refocusing measures during the COVID-19 pandemic in Indonesia that attempted to hasten the pandemic's handling. It has implications for fostering economic growth from efforts to slow the growth rate of government consumption spending, personnel spending, and the existence of a social safety net program that affects the realization of spending on goods and services both in collective and individual consumption expenditures as a result of the budget refocusing policy related to the state revenue and expenditure budget as well as the regional revenue and expenditure budget.